基于ANSYS的承压齿盘结构优化设计 - 韩维涛; 张亚新 (Jixie chuandong)
Optimization design has been the field comparatively paid close attention to in the province of engineering all the time.By the instance of pressured dentate disc basic thought and key step realized on ANSYS in structure optimization design has been introduced.The result indicates that the rational optimization design can improve the security and economy,and information is provided for improving design of all kinds of machinery parts.